2015
DOI: 10.1007/s00259-015-3193-4
|View full text |Cite
|
Sign up to set email alerts
|

Subacute haematotoxicity after PRRT with 177Lu-DOTA-octreotate: prognostic factors, incidence and course

Abstract: PurposeIn peptide receptor radionuclide therapy (PRRT), the bone marrow (BM) is one of the dose-limiting organs. The accepted dose limit for BM is 2 Gy, adopted from 131I treatment. We investigated the incidence and duration of haematological toxicity and its risk factors in patients treated with PRRT with 177Lu-DOTA0-Tyr3-octreotate (177Lu-DOTATATE). Also, absorbed BM dose estimates were evaluated and compared with the accepted 2 Gy dose limit.MethodsThe incidence and duration of grade 3 or 4 haematological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 30 publications
(32 reference statements)
14
116
0
2
Order By: Relevance
“…Weight loss in animals is often an indicator of toxicity, and the most radiosensitive organs for PRRT are the bone marrow and kidney [8, 28, 29]. In this study, we observed severe weight loss in 67% of animals exposed to high-dose 213 Bi-DOTATATE (cumulative 33.1 ± 3.7 MBq), within 2 weeks after treatment, indicating acute toxicity.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Weight loss in animals is often an indicator of toxicity, and the most radiosensitive organs for PRRT are the bone marrow and kidney [8, 28, 29]. In this study, we observed severe weight loss in 67% of animals exposed to high-dose 213 Bi-DOTATATE (cumulative 33.1 ± 3.7 MBq), within 2 weeks after treatment, indicating acute toxicity.…”
Section: Discussionmentioning
confidence: 47%
“…The mass of injected peptide influences the pharmacokinetics (PK) and absorbed doses in organs and tumors [6]. Therefore, the mass of injected peptide should be optimized to deliver efficacious tumor doses while avoiding toxic absorbed dose to organs, especially to the dose-limiting organs the kidneys and bone marrow [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…In large trials, grade 3 or 4 hematologic toxicity has been reported in 3%-14% of the patients (26)(27)(28). Long-term myelotoxicity in the form of myelodysplastic syndrome or acute leukemia is a rare and severe adverse event associated with PRRT, occurring in 1%-2% of patients (29).…”
Section: Safetymentioning
confidence: 99%
“…In addition, overall, there was no observed dose-response effect on serious (permanent) bone marrow toxicity, and it was believed to be unlikely that the widely used bone marrow limit of 2 Gy had any validity with regard to this radioligand (43). Finally, this experience also demonstrated that PRRT with [ 177 Lu-DOTA,Tyr 3 ]octreotate, administered in conjunction with appropriate amounts of amino acids for kidney protection, had virtually no renal toxicity (44).…”
Section: Lu Prrt Is Developedmentioning
confidence: 64%